(untitled) (Bangladesh Journal of Medical Science, 2014)
Objective: This study aimed at investigating the effect of high sucrose diet on male reproductive function and if Nigerian honey could exert a protective role. Methods: Twenty-four (24) rats were randomly divided into four equal groups of six animals and given water (control); honey (H); high sucrose solution (30%w/v) (HSS); and both high sucrose solution (30%w/v) and honey (HSS+H). Each rat on honey received a daily dose of 10ml honey/kg/5ml of distilled water. Food intake, body weight, organ weight, fasting blood glucose, LH, FSH, testosterone and sperm functions were assessed. Results: This revealed that sperm motility (p<0.05) and count increased in the HSS+ H and H- fed rats compared with HSS fed and control rats. Head and tail abnormalities sperm were also significantly reduced in the H fed rats (p<0.05).MDA level in the liver and not in the testes was significantly increased in the HSS fed rats compared with control while SOD activity was significantly increased in HSS+H rats compared with the HSS fed rats. Conclusion: The results indicate that sucrose feeding impact negatively on sperm function while Nigerian honey supplementation confers protective function on male reproduction. DOI: http://dx.doi.org/10.3329/bjms.v13i2.18301 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.180-189